Foreign Direct Investment in Indonesia and Its Macroeconomic Dynamics - Candy Candy; Charles Ng; Isnaini Nuzula Agustin (Penerbit Goodwood, 2026)
Purpose: This study investigates the effects of exchange rates, interest rates, human capital, and Gross Domestic Product (GDP) on Foreign Direct Investment (FDI) inflows in Indonesia in both the short and long run. Research Methodology: This study employs secondary monthly time-series data from January 2014 to June 2024 and Applies the Autoregressive Distributed Lag (ARDL) approach to examine the dynamic relationships among variables. The analysis was conducted using EViews 12, supported by stability tests and multicollinearity diagnostics. Results: The ARDL bounds test confirms the existence of a stable long-run cointegrating relationship among the variables. The estimation results show that GDP has a positive and statistically significant effect on FDI in both the short and long run. In contrast, the exchange rate, interest rate, and human capital do not exhibit statistically significant effects on FDI in either period. Model stability tests indicate that the ARDL specification is structurally stable, although a relatively high degree of multicollinearity is observed between human capital and GDP. Conclusions: The findings indicate that Foreign Direct Investment (FDI) inflows in Indonesia are primarily driven by economic growth, as reflected by Gross Domestic Product (GDP), while other macroeconomic variables play a limited direct role. Limitations: This study was limited by multicollinearity issues and the use of a relatively narrow set of macroeconomic variables. Contributions: This study provides empirical evidence on the determinants of FDI in Indonesia using the ARDL framework and offers policy-relevant insights emphasizing growth-oriented investment strategies.